Digester tipe Balon untuk Pembangkit Listrik Tenaga Biogas di Peternakan Sei Temiang Batam - Qoriatul Fitriyah; Dedi Irawan; Muhammad Prihadi Eko Wahyudi (JURNAL INTEGRASI, 2018)
Sei Temiang Livestock in Batam, produce roundabout ±50 m3 of cow faeces each month. Usually, some of this waste is taken away by villagers to be used as raw material of fertilizer. To increase its value, the excrement can be utilized as source of alternative energy before the remnants are applied as organic manure. This research use baloon type as the digester of biogas power plant due to reasons such as simple installation, easy to be overhauled, and the cost is quite affordable. This prototype use a mixture of cow excrement and water with proportion of 1:1. Gas equivalent to 624 litre can be gained from 1 plastic drum which is able to turn on the electricity for 35 minutes with power capacity of 700 watts.